Training Of Using Used Accessories Into New Accessories As A Business Opportunity - Erlina Novianti; Silviana Amanda A.T; Ratih Candrastuti (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
In general, women have a lot of accessories, but sometimes the accessories have been damaged or the model is dated. Recycling accessories, it can be done by reusing used accessories that can be created into new accessories. This community service activity was organized by the Trisakti University Photography Study Program targeting the wives of the Air Force soldiers at the Iswahjudi Madiun Air Base. This training aims to provide creative and educational activities about reprocessing unused accessories into new accessory products that can be sold. The method used is experimental, the community service coordinator and participants will practice directly making accessories from used materials. The benefit of this activity is to bridge between the institution and the community so that there is a positive institutional contribution in society and provide knowledge in recycling goods that are around us and provide skills in making accessories that can be used as business opportunities.